2001
DOI: 10.1152/ajpendo.2001.281.4.e782
|View full text |Cite
|
Sign up to set email alerts
|

The vagus is inhibitory of insulin secretion under fasting conditions

Abstract: The involvement of the vagus in the insulin response during the early phase of absorption of a meal has been demonstrated recently. The extent of this vagal influence was investigated during fasting in an anesthetized porcine model. Portal and systemic insulin were evaluated together with glycemia during cooling and sectioning of both cervical vagal trunks in 12 splanchnicotomized or sham-operated pigs. In sham-operated animals, portal and systemic insulin were significantly and reversibly increased by cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…Contrary to our findings, previous reports have demonstrated that vagotomy did not alter insulin clearance in lean pigs [ 23 ]. This suggests that vagotomy-induced reduction in insulin clearance is a phenomenon observed only in an obese mouse model, probably because they experienced malnutrition during early life.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, previous reports have demonstrated that vagotomy did not alter insulin clearance in lean pigs [ 23 ]. This suggests that vagotomy-induced reduction in insulin clearance is a phenomenon observed only in an obese mouse model, probably because they experienced malnutrition during early life.…”
Section: Discussioncontrasting
confidence: 99%
“…Biochemical analyses were performed on this serum and urine by routine clinical laboratory methods. Additionally, plasma insulin, amino acid concentrations of plasma and urinary samples were measured in 3 NP and 5 HP piglets at d16 as previously described [12,13] . Amino acid concentrations were not determined in plasma and urinary samples of HP-sup piglets at d16 because of insufficient plasma and urine samples.…”
Section: Sample Collection and Biological Analysesmentioning
confidence: 99%
“…In line with this assumption, plasma insulin was lower in SDA than in sham obese rats. It needs to be determined whether this effect is due to the loss of vagal efferent signals that stimulate insulin secretion or to the disruption of afferent neurons that transmit information to the brain, which then reflexively inhibits insulin release via sympathetic efferents to the pancreas, or to a combination of both (5,16). Hyperinsulinemia correlates with body weight and, in particular, body fat (e.g., Ref.…”
mentioning
confidence: 99%